1994
DOI: 10.1128/iai.62.5.2085-2093.1994
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth factors on Escherichia coli alpha-hemolysin-induced mediator release from human inflammatory cells: involvement of the signal transduction pathway

Abstract: Previously, we have shown that Escherichia coli alpha-hemolysin represents a potent stimulus for inflammatory mediator release (02release, ,-glucuronidase release, and leukotriene generation) from human polymorphonuclear granulocytes (PMN) as well as for histamine release from a human lymphocyte-monocytebasophil cell suspension (LMB). In contrast, the E. coli alpha-hemolysin leads to a downregulation of cytokine release (interleukin 6 , tumor necrosis factor alpha, and IL-1il) from human LMB. This study was un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 23 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Investigations into the effect of acylation on the ability of sublytic concentrations of HlyA to stimulate a host cell response have been complicated, perhaps significantly, by the presence of LPS in toxin preparations. At least the major component of HlyA binding to granulocytes appears to be non-receptor mediated, with subsequent triggering of the respiratory burst presumably not through the occupancy of a receptor but through a short-circuiting of the classical signal transduction pathway (103,165). Acylation may therefore enhance protein-protein interactions between HlyA and components of a signal transduction pathway, perhaps by targeting to detergent-resistant domains (Fig.…”
Section: Effects Of Hlya Toxin On Host Cell Signalling and Cytokine Pmentioning
confidence: 99%
“…Investigations into the effect of acylation on the ability of sublytic concentrations of HlyA to stimulate a host cell response have been complicated, perhaps significantly, by the presence of LPS in toxin preparations. At least the major component of HlyA binding to granulocytes appears to be non-receptor mediated, with subsequent triggering of the respiratory burst presumably not through the occupancy of a receptor but through a short-circuiting of the classical signal transduction pathway (103,165). Acylation may therefore enhance protein-protein interactions between HlyA and components of a signal transduction pathway, perhaps by targeting to detergent-resistant domains (Fig.…”
Section: Effects Of Hlya Toxin On Host Cell Signalling and Cytokine Pmentioning
confidence: 99%
“…It is crucial to find other safe and effective treatment options to manage G-CSF-induced bone pain. Konig and Konig 11 suggested that G-CSFs play a role in the inflammatory pathway by increasing histamine release. We present the first case report that delineates loratadine use to prophylax against severe pegfilgrastim-induced bone pain.…”
Section: Discussionmentioning
confidence: 99%